Relationship between breastfeeding practices and nutritional status of children aged 6-24 months in South-west Nigeria - Abolurin OO; Oyelami AO; Oseni SB; Akinlosotu MA; Sodeinde KJ; Adekoya AO (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2021)
Background: Breastfeeding is the ideal form of nutrition for the healthy growth of infants, and it reduces the risk of malnutrition and several childhood morbidities. Objectives: To assess the breastfeeding practices of mothers and the relationship between these practices and the nutritional status of their children. Methods: It was a descriptive, hospital-based, cross-sectional study that involved children aged six to 24 months in Ilesa, Osun State, Nigeria. Socio-demographic characteristics and breastfeeding practices were documented, anthropometric measurements were obtained, and nutritional status was determined for the children. Underweight, stunting and wasting were defined as z-score < -2 for the weight-for-age, length-for-age and weight-for-length, respectively. A child was taken to be undernourished if any of underweight, stunting or wasting was present. Results: Fifteen (3.6%) of the 420 children studied had mixed feeding from birth, while 273 (65.0%) were exclusively breastfed for six months. Two hundred and sixty-eight (63.8%) of them were still breastfeeding at the time of the study, while 152 (36.2%) had stopped breastfeeding. Nearly one-quarter (103/420; 24.5%) of the children were undernourished. A significantly lower proportion of children who had exclusive breastfeeding were undernourished, compared to those who were not exclusively breastfed (p = 0.033). Exclusive breastfeeding was independently associated with reduced odds of undernutrition (OR = 1.62, 95% CI = 1.02-2.57, p = 0.039). Conclusion: Exclusive breastfeeding for six months significantly reduces the risk of undernutrition among young children.